ANALYSIS OF PERSONAL BRANDING IN VIRTUAL WORLD THROUGH LANGUAGE - Swasono, Endratno Pilih; Kaltsum, Kamillah Ariqoh; Nurlaili, Rahma Dila (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research’s main purpose is to find the construction of identity social media users in the virtual world through language according to Goffman theory. The researchers use qualitative methods, which in the process the researchers observing a social media account followed by analyzing based on the theory. In this research, there are several steps required collecting data from social media, analyzing the data that shows personal identities, and through personal branding that they create with language, for example, such as bio on social media, special terms that characterize them, caption, and also content. Our study revealed that language can be a tool of personal branding by creating and expressing new social identity through the words or phrases they use to communicate with society.